2017
DOI: 10.1039/c7ra10034e
|View full text |Cite
|
Sign up to set email alerts
|

Ag+, Fe3+and Zn2+-intercalated cadmium(ii)-metal–organic frameworks for enhanced daylight photocatalysis

Abstract: A new generation MOF photocatalyst capable of harvesting day light was fabricated by intercalating chosen metal ions onto a Cd(ii) metal–organic framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The pristine MOF doped or incorporated with another metal provide a scope to tune the electronic band gap. Recent studies show that the incorporation of iron as second metal in MOF decreases the band gap of parent MOF and enhanced its absorption into visible region . The band gap values of MIL‐53 and MOF‐5 are 2.6 eV and 3.5 eV whereas the BMOF in present work assessed band gap value ca.…”
Section: Figurementioning
confidence: 53%
See 1 more Smart Citation
“…The pristine MOF doped or incorporated with another metal provide a scope to tune the electronic band gap. Recent studies show that the incorporation of iron as second metal in MOF decreases the band gap of parent MOF and enhanced its absorption into visible region . The band gap values of MIL‐53 and MOF‐5 are 2.6 eV and 3.5 eV whereas the BMOF in present work assessed band gap value ca.…”
Section: Figurementioning
confidence: 53%
“…Recent studies show that the incorporation of iron as second metal in MOF decreases the band gap of parent MOF and enhanced its absorption into visible region. [22] The band gap values of MIL-53 and MOF-5 are 2.6 eV [23] and 3.5 eV [24] whereas the BMOF in present work assessed band gap value ca. 1.9 eV which suggest that the presence of second metal decrease the band gap.…”
mentioning
confidence: 52%
“…During photocatalysis, a series of oxygen species including singlet oxygen ( 1 O 2 ), superoxide radical ( • O 2 À ), and hydroxyl radical ( • OH) with high oxidizing ability were formed from the photoinduced electrons/holes to degrade various organic pollution. [42,142,196,238,239] In addition, photogenerated holes could also directly participate in the oxidative degradation process. [39] However, different from the photocatalysis organic transformation, • OH radicals as the most oxidative species were commonly applied in the degradation of pollutants.…”
Section: Degradation Of Water Pollutantsmentioning
confidence: 99%
“…Even, posterior studies demonstrated the instability of MOF-5 in water systems [227]. More recently, Surib et al [234] intercalated several metal ions (Ag + , Fe 3+ , and Zn 2+ ) into the porous framework of a Cd-MOF by ion-exchange, yielding a new series of photocatalysts used for the removal of 2-chlorophenol under direct daylight illumination. All of the tested modified-MOFs were more active than the common TiO 2 , although when intercalated with Fe 3+ they achieved the highest conversion value, 93% after 5 h of reaction.…”
Section: Photodegradation Of Priority Pollutantsmentioning
confidence: 99%